Evaluation of Stunting Countermeasures Strategies in Indonesia - Azhara, Ratu Raisya Aghnia; Deliarnoor, Nandang Alamsah; Sagita, Novie Indrawati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Stunting is a major health problem for toddlers in Indonesia. To prevent and overcome stunting in Indonesia, the central and regional governments have established various policies and programs to accelerate stunting reduction. This study aims to evaluate government policies and programs from existing studies on the government's strategy for tackling stunting cases in Indonesia. This study used a systematic review method on case study journals indexed by Sinta with the keyword